Gaseous, Physicochemical and Microbial Performances of Silicon Foliar Spraying Techniques on Cherry Tomatoes - Mohammad Zahirul Islam; Mahmuda Akter Mele; Ho-Min Kang (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2018)
Silicon (Si) foliar spraying techniques (17 mM Si leaf and whole plant) were applied to determine the effect of gaseous, physicochemical and microbial activities on cherry tomatoes. Whole treated tomato plant showed significantly (p ≤ 0.05) the lowest respiration and ethylene production occurred during harvest time and after storage. The lowest fresh weight loss, fungal incidence and microbial activity were observed in whole plant treated tomatoes. In addition, the longest shelf life 24 days and the highest firmness were maintained by whole plant Si treated tomatoes. A higher vitamin C content was found in the whole Si treated tomato plants compared to Si leaf or no treated tomatoes. In addition, in the whole Si treated tomato plant showed the lowest soluble solid content by suppressing the color development. Based on the above results, whole plant Si treatment may be a useful technique to maintain respiration, ethylene production, firmness, shelf life and microbial activity of cherry tomatoes.